The relationship between technique and high knee loads related to injury in landing tasks - Dempsey, A.; Elliott, B.; Lloyd, D. (Journal of Science and Medicine in Sport, 2011)
Introduction: Athletes suffering an anterior cruciate ligament (ACL) injury tend to exhibit similar body postures. These body postures have been associated with increased valgus and internal rotation moments at the knee in sidestep cutting. However this relationship between full body postures and knee loads has not been investigated in landing. Catching a ball in different overhead positions during ball marking in Australian football may affect landing postures and the aforementioned knee joint moments. This study investigated these possible relationships. It was expected that some joint postures similar to those observed during actual injuries, would be associated increased knee loads during landing. Methods: Twenty five healthy male team sports athletes performed four variations of a landing task that mimicked overhead marking of a ball in Australian Football. Full body kinematics were identified at initial contact. Peak flexion, valgus and internal rotation moments at the knee measured during early landing were normalized to mass and height and statistically compared. Intra-participant correlations were performed between all kinematics and each moment. Mean slopes for each correlation were used to identify the existence of relationships between full body kinematics and knee joint moments. Results: Increased knee valgus moments were correlated with increased knee flexion, hip flexion, torso lean and torso rotation towards the support leg, and foot and knee external rotation. Increase internal rotation moments, which were similar for all tasks, were correlated with reduced hip abduction and external rotation, increased ankle inversion, knee external rotation and torso lean away from the support leg. Conclusion: Specific body postures were associated with increased knee joint moments related to ACL injuries. The postures linked to injury, specifically a leaning torso and external rotation at the knee, are similar to those observed during ACL injuries. Higher knee moments being associated with increased knee flexion is contrary to what has previously been reported the literature and further investigation is needed into this relationship Training athletes to avoid high loading postures has reduced knee loads in sidestepping, and future work should investigate is similar results can be achieved during landing tasks.